Social crowdfunding project: Do project quality and trust matter? / Wan Nur Fazni Wan Mohamad Nazarie ... [et al.] - Wan Mohamad Nazarie, Wan Nur Fazni; Williams, Russell; Abdullah Thaidi, Hussein 'Azeemi; Muhammad, Izlawanie (Research Management Centre (RMC), 2023)
In the digital age, crowdfunding has emerged as a prominent way of raising funds, embraced by entrepreneurs and project owners who seek financial backing for their ventures. Through crowdfunding platforms, certain individuals have witnessed the success of campaigns that draw significant funds, enabling the realisation of their projects. However, it's essential to know that not all crowdfunding efforts are equal. While some campaigns may struggle to meet their funding goals, others exceed expectations by a considerable margin. Like other online platforms, trust plays a crucial role in establishing and nurturing relationships within crowdfunding campaigns. Project owners seek confidence that donations contributed by supporters for their social projects are used for their intended purposes. Additionally, the quality of projects has a substantial influence. Hence, the primary objectives of this study are to investigate how project quality (video and logo) could potentially influence crowd trust when considering donations. By examining these factors, we aim to gain valuable insights into the dynamics of crowdfunding campaigns. Using a sample of 420 participants residing in the Klang Valley, this study empirically demonstrated that project quality significantly contributes to enhancing crowd trust. The findings presented in this paper hold the potential to offer valuable insights to project owners aiming to augment their funding goals within crowdfunding projects.